Diamond-Blackfan anaemia in a girl with a de novo balanced reciprocal X;19 translocation. Issue 9 (September 1997) - Gustavsson, P; Skeppner, G; Johansson, B; Berg, T; Gordon, L; Kreuger, A; Dahl, N
Abstract : A 7 year old girl is described with congenital hypoplastic anaemia (Diamond-Blackfan anaemia, DBA) and an apparently balanced reciprocal translocation, 46, XX, t(X;19)(p21;q13). The girl has associated features including short stature, unilateral kidney hypoplasia, and a branchial cyst. Fluorescent in situ hybridisation (FISH) studies with 19q specific cosmids showed that the chromosome 19 breakpoint is located between the RYR1 and the XRCC11 loci spanning a physical region of 5 Mb. There is no family history of DBA and the parents and two healthy sibs have normal karyotypes. This is the first report of a balanced translocation associated with DBA and we suggest that the distinct phenotype has resulted from a de novo disruption of a functional gene. DBA can be inherited as an autosomal trait and our observation may indicate a candidate gene for the disorder in the 19q13 region.